Good chemistry : (McGraw-Hill, 2004)
The development of Valium by Roche Pharmaceutical and the entire benzodiazepine group of active substances was among the greatest accomplishments in 20th-century pharmacology. Good Chemistry combines a detailed account of this momentous development with an engaging biography of Leo Sternbach, the brilliant chemist who invented Valium and whose achievements heralded the beginning of a new era in research and therapeutics. This thought-provoking biographical history: Tells the fascinating life story of one of the 20th century's premier chemists Traces the developments that led to the invention of Valium Provides a cultural history of Valium and its impact on society